Evaluation of Three Types of Iron Drop on Enamel Microhardness and Resistance of Primary Tooth in Acidic Environment: An In Vitro Study - SAMANEH HEMMATI; Hamed Tari; Jaber Mosavi; mohadese shakerian (Mashhad University of Medical Sciences, 2022)
Introduction: Iron drops are often prescribed to children less than 2 years of age. Due to their low pH, these drops may soften the enamel and accelerate its destruction. The present study aimed to evaluate the enamel hardness of deciduous teeth after being exposed to various iron drops.Material and Methods: A total of 48 healthy deciduous anterior teeth were randomly assigned to four groups (n=12 in each group). The samples were exposed to three drops of Sideral iron, Ferrosomal, and Ferrous sulfate for 5 min. Surface hardness was measured before and after iron drop exposure. Four groups were exposed to HCL, and the obtained data were analyzed using the least significant difference (LSD) test and analysis of variance (ANOVA).Results: In all groups, a decrease was observed in the surface hardness of surface enamel. In the Sideral group, the average initial hardness was 358.81, the secondary hardness was 337.23, and the tertiary hardness was 221.19. In the Ferosomal group, the average primary hardness was 375.67, the secondary hardness was 336.80, and the tertiary hardness was 208.23. In the Ferrous sulfate group, the average initial hardness was 383.41, the secondary hardness was 301.73, and the tertiary hardness was 149.13. Therefore, the three groups statistically differ before and after the iron drop. After the use of iron drop in an acidic environment, there was a statistical difference between Ferrous sulfate and two other drops (P<0.05). Between Sideral and Ferosmal, the difference was not significant (P=0.864).Conclusion: As evidenced by the results of this study, it can be concluded that all three types of iron droplets in the environment, similar to human saliva, significantly reduced the hardness of enamel. In an acidic environment, all three types of iron drop reduced the hardness of the enamel of deciduous teeth. The Ferrous sulfate group demonstrated the most significant reduction in the microhardness of the enamel, and the Sideral group had the most negligible decrease in enamel hardness.